1983
DOI: 10.1002/jsfa.2740340112
|View full text |Cite
|
Sign up to set email alerts
|

Volatile aroma constituents of kiwifruit

Abstract: The volatile constituents of kiwifruit (Actinidia chinensis Planch.) have been investigated. The volatiles were collected and concentrated using vacuum steam distillation and freeze concentration. The concentrated distillate was analysed by gas chromatography, gas chromatography-mass spectrometry and reaction gas chromatography. Apart from methyl benzoate, all the components identified were alkyl and alkenyl esters, alcohols, aldehydes and ketones. The most abundant component was trans hex-2-enal. Odour evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 7 publications
0
28
1
Order By: Relevance
“…The apples (2.1 kg) were peeled, cored and sliced (1-3 mm thick) and placed into a 3 litre reaction vessel (Quickfit) fitted for vacuum steam distillation (Young et al 1983). No water was added and no stirring was done.…”
Section: Isolation Of Flavour Volatilesmentioning
confidence: 99%
“…The apples (2.1 kg) were peeled, cored and sliced (1-3 mm thick) and placed into a 3 litre reaction vessel (Quickfit) fitted for vacuum steam distillation (Young et al 1983). No water was added and no stirring was done.…”
Section: Isolation Of Flavour Volatilesmentioning
confidence: 99%
“…It is rich in potassium, vitamin C, A and E and carotenoids [10]. Several studies [11][12][13] indicate that there are more than 70 volatile compounds involved in the composition of kiwi, mainly C6 aldehydes, alcohols and esters, being the aldehydes more prevalent in unripe fruit, and esters in the ripe fruit. Hexanal, trans-2-hexenal and ethyl butanoate are the compounds more often reported.…”
Section: Introductionmentioning
confidence: 99%
“…A GC-sniffing study showed that acetaldehyde, hexanal, ethyl butanoate and hex-E2-enal had odour activity in macerated fruit of 'Hort16A' ). Young et al (1983) reported that hex-E2-enal, ethyl butanoate, methyl benzoate and hexanal were important contributors to the aroma and flavour of 'Hayward' (A. deliciosa). Studies on the causal effects of selected flavour volatiles on the intensity of sensory attributes in 'Hayward' showed that ethyl butanoate, methyl benzoate and hexanal had positive correlations with sweet aroma and flavour (McMath et al 1991;.…”
Section: 'Flavour Impact' Volatiles Of a Chinensis Fruitmentioning
confidence: 98%
“…Many of the earlier studies on kiwifruit aroma focused on the composition of volatile compounds. Up to 90 volatiles were identified from fruit of 'Hayward' (Young et al 1983;Young and Paterson 1985;Takeoka et al 1986;Paterson et al 1991;Perera et al 1998). Between 40 and 80 volatiles were detected from fruit of A. arguta genotypes (Matich et al 2003).…”
mentioning
confidence: 99%